Journal Of Analysis Of Understanding, Calculation Of Income On Corn (Zea Mays L) In The Rate We Farmers Group, Bhera Village, Mego District, Sikka Regency (International Forum of Researchers and Lecturers, 2025)
Corn (Zea mays L) as a Strategic Agricultural Commodity in Sikka Regency: Income and Feasibility AnalysisCorn (Zea mays L) is one of Indonesia’s national commodities,significantly contributing to state revenue and employment opportunities. The demand for corn is projected to continue increasing, making it a potentially profitable commodity in the future.Corn is considered oneof leading agricultural commodities in Sikka Regency, cultivated both in paddy fields and drylands during the rainy season. Farmers believe that growing corn is more profitable than other crops, making it a highly attractive option for cultivation.The purpose of this extension activity is to provide farmers with an understanding of how to analyze income and the feasibility of corn farming in Sikka Regency. The research method employed is descriptive qualitative analysis. The study was conducted in one village, namely Bhera Village, located in Mego Subdistrict, Sikka Regency. This village was chosen based on the consideration that it has a significant number of corn farmers.The research results show that corn farming in Bhera Village, particularly in the Rate Wa farmer group, generates an income of IDR 21,000,000 per hectare per planting season. This farming activity is considered feasible because it has an R/C ratio of 1.45, which is greater than 1, indicating that for every IDR 1 spent, the return is IDR 1.45. Therefore, corn farming in this area is profitable and feasible to pursue.